Conflicts and Wars in Post-Colonial African: Analysis of Causes and Effects on Africa’s Development - Nduka Lucas Oluka; Osuji Zephaniah Edo; Irikefe Omamuyovwi Afonughe (Universitas Negeri Makassar, 2025)
The post-colonial African society is inarguably disposed to internal conflicts, most of which have resulted to full-brown civil wars. The major causes of some of these conflicts have been traced to the events that happened during colonial rule, such as implantation and promotion of ethnic and religious consciousness among the people by the European colonialists. Most perturbing is the fact that colonial legacies in the continent continue to dominate post-independence relationship, and weakened cohesion and unity among the diverse nationalities in African society. Solutions to these delusions propagated, first, by the European colonial masters, and now by Africans against Africans, have defied meaningful solutions as conflict persists in most countries in Africa. It is on these conditions that this study interrogates the similarities in the causes of conflicts and wars in post-colonial Africa, and how these conflicts affect development. Qualitative inquiry was adopted as the study’s research design. The study relied extensively on secondary sources of data such as textbooks, journal articles, dailies, periodicals, internet materials, among others. Failed-State theory was adopted as its theoretical framework. The Study suggests among others that Africa post-colonial states should assiduously delink from their self-notions of colonial legacies and embrace the reality of their internal polities. Africa should also shun self-imposed ethnic consciousness and other internal factors causing conflicts and wars. Fairness and equity in distribution of commonwealth should be prioritised in order to prevent issue of sectional marginalisation that is consistently one of the major factors promoting conflict in African States.